The Influence of Problem Based Learning Model (PBL) Through Picture Series Media to Improve Students Speaking Ability Seen from Students Learning Style in English Lesson of XI Grade in SMA N 1 Sumber Cirebon - Muhadharah, Umarah; Haryono, Haryono; Rifai RC, Achmad (Innovative Journal of Curriculum and Educational Technology, 2018)
Each student has his learning style in understanding, comprehending, until practicing his already owned knowledge. Specifically, in learning the English language, all students must have the potential motivation or dominant ability affected by surroundings, habits, and also science and technology. Learning English lesson for the eleventh grader of SMAN 1 Sumber still tended to use the conventional method without supporting the result of students’ speaking ability. This research has purposed to (1) analyze the effectiveness of PBL model through picture series media to improve students’ speaking ability seen from students learning style, (2) analyze the effectiveness of learning styles to improve students’ speaking ability, and (3) analyze the interaction between learning style of the students with PBL model to improve students’ speaking ability. It was a semi-experimental model by using treatment by level 2x2 factorial design. The population was XI grader of Senior High School 1 Sumber. The samples were two randomly chosen classes: XI MIA 4 and XI MIA 7. The data of the research were analyzed by SPSS 17.0 and Two Ways ANOVA. The findings showed improvement of English speaking ability seen from student learning styles and the learning styles were effective to improve the English speaking ability of the student. There was an interaction between learning style with the PBL model in improving the English speaking ability of the students. Seen from the elaboration above, it could be explained that the intervention could improve the English speaking ability of the student. The findings would help students and teacher to recognize student learning styles and the teachers could select appropriate media and learning method to improve student learning achievements.